ANALISIS KESESUAIAN RTRW PADA BIDANG PERTAMBANGAN BERDASARKAN RTRWP KALIMANTAN SELATAN DAN RTRWK DI KABUPATEN TAPIN - Wibisono, Raden Rafiq Sepdian Fadel; Mahreda, Emmy Sri; Biyatmoko, Danang; Hafiziannor, Hafiziannor (Universitas Lambung Mangkurat, 2023)
As a province rich in natural resources, especially mining products, South Kalimantan (South Kalimantan) is also not free from problems in the environmental sector. The massive mining activity in the province of South Kalimantan has caused environmental damage and loss of land cover in South Kalimantan. This happened because 41 percent of the Meratus forest and other forests in South Kalimantan were already burdened with mining permits. Efforts to balance the use of natural resources and the environment are through spatial planning based on the achievement of environmental function sustainability. The purpose of this study is to analyze the suitability of the RTRW, analyze the factors that influence the suitability of the RTRW, and analyze how big the positive and negative impacts of the suitability of the RTRW are. This research was conducted by making a land use map that aims to see how the situation is in the field and compare it with a planning map using a Geographic Information System. The results of the comparison of the planning map and the conditions in the field show the suitability of land use. The results obtained using Tapin's RTRWK in IUP MINERBA are 15.22%, which means that the implementation of space utilization is not appropriate. The influencing factors are the development of settlements which are increasing every year very rapidly due to the increasing population. The positive impact is that the companies have helped to repair village roads that are used by the community to reduce the number of unemployed, increase regional income levels, and improve the economic welfare of the surrounding community. The negative impact is environmental damage and social conflict in the community, increasing the vulnerability to traffic accidents due to increased road users.